2021
DOI: 10.1021/acsabm.1c00601
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-like Self-Assembly of a Hydrophobic Cell-Penetrating Peptide and Its Use as a Carrier for Nucleic Acids

Abstract: Cell-penetrating peptides (CPPs) are a topical subject potentially exploitable for creating nanotherapeutics for the delivery of bioactive loads. These compounds are often classified into three major categories according to their physicochemical characteristics: cationic, amphiphilic, and hydrophobic. Among them, the group of hydrophobic CPPs has received increasing attention in recent years due to toxicity concerns posed by highly cationic CPPs. The hexapeptide PFVYLI (P, proline; F, phenylalanine; V, valine;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 77 publications
(138 reference statements)
0
26
0
Order By: Relevance
“…The strong correlation observed for µm-sized aggregation further emphasizes a fundamental common principle for infectivity enhancement of peptides: The hydrophobic surface properties may not only be a driving force for peptides to form fibrils, [72,73] increase fibril-fibril association [42,74] which leads to µmsized aggregates, but also a prerequisite to bind and capture viral particles. An interplay between hydrophobicity, electric charge, and anions in buffer is well-known to control the formation of hierarchical structures, such as amorphous aggregates or amyloid fibrils.…”
Section: Discussionmentioning
confidence: 92%
“…The strong correlation observed for µm-sized aggregation further emphasizes a fundamental common principle for infectivity enhancement of peptides: The hydrophobic surface properties may not only be a driving force for peptides to form fibrils, [72,73] increase fibril-fibril association [42,74] which leads to µmsized aggregates, but also a prerequisite to bind and capture viral particles. An interplay between hydrophobicity, electric charge, and anions in buffer is well-known to control the formation of hierarchical structures, such as amorphous aggregates or amyloid fibrils.…”
Section: Discussionmentioning
confidence: 92%
“…Droplets from this bacterial suspension were spread on the surface of freshly cleaved mica, and fixed with 4 % PFA following protocols used before by our group. [45][46][47] Liquid chromatography coupled to mass spectroscopy with electrospray ionization (LC/ESI-MS): The samples were characterized by LC/ESI-MS to identify the main byproducts in the samples. The experiments were performed on a Waters Alliance 2695 Separations Module coupled with a Waters 2996 PDA detector and a Waters 3100 Mass Detector.…”
Section: Methodsmentioning
confidence: 99%
“…To reduce imaging issues related to the presence of components from the broth, droplets from the culture were suspended in saline solutions. Droplets from this bacterial suspension were spread on the surface of freshly cleaved mica, and fixed with 4 % PFA following protocols used before by our group [45–47] . Liquid chromatography coupled to mass spectroscopy with electrospray ionization (LC/ESI‐MS) : The samples were characterized by LC/ESI‐MS to identify the main byproducts in the samples.…”
Section: Methodsmentioning
confidence: 99%
“…[ 58 ] Additionally, the self‐assembly of peptide‐nucleic acids noncovalent complexes exhibited remarkable amyloidogenic features. [ 59 ] It was identified that co‐delivery of apoptotic peptide and DNA sequences as apoptosis‐associated therapy was capable of killing resistant breast cancer cells. [ 60 ] The integration of FAM‐labeled DNA and paclitaxel‐locked nucleic acid (LNA) monomer allowed the assembly and formation of spherical nanomicelles.…”
Section: Biological Materials Interacting With Nucleic Acidsmentioning
confidence: 99%